Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1167/iovs.12-11509
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Cross-Linking Using Rose Bengal and Green Light to Increase Corneal Stiffness

Abstract: PURPOSE. Photochemical cross-linking of corneal collagen is an evolving treatment for keratoconus and other ectatic disorders. We evaluated collagen cross-linking by rose bengal plus green light (RGX) in rabbit eyes and investigated factors important for clinical application.METHODS. Rose bengal (RB, 0.1%) was applied to deepithelialized corneas of enucleated rabbit eyes for 2 minutes. The diffusion distance of RB into the stroma was measured by fluorescence microscopy on frozen sections. RB-stained corneas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 41 publications
7
164
1
1
Order By: Relevance
“…16,24 The photoinitiator used is a standard of eye care used topically, 17 and experimental studies in rabbit eyes have revealed that it is nontoxic intracapsularly and does not compromise corneal endothelial cell integrity. 18 Exposure times and fluences of the green light used are comparable to those used in two other applications of green light and RB, namely, photobonding amniotic membrane to cornea and photo-crosslinking of the cornea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,24 The photoinitiator used is a standard of eye care used topically, 17 and experimental studies in rabbit eyes have revealed that it is nontoxic intracapsularly and does not compromise corneal endothelial cell integrity. 18 Exposure times and fluences of the green light used are comparable to those used in two other applications of green light and RB, namely, photobonding amniotic membrane to cornea and photo-crosslinking of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…14 Corneal collagen photo-crosslinking has also been demonstrated with other photosensitizers, such as Rose Bengal (RB) and green light irradiation. 15,16 One advantage of the use of RB is that it is a US Food and Drug-approved compound widely used in ophthalmology, for example, in dry eye staining tests. 17 In addition, intracapsular use of RB was shown to be nontoxic in rabbit eye models, actually reducing the rate of posterior capsular opacification.…”
mentioning
confidence: 99%
“…Of note, this treatment did not induce the keratocyte apoptosis that is seen with riboflavin and UVA treatment. Due to the more shallow penetration of Rose Bengal, the cross-linking effect is more anterior in the stroma; however, this may be beneficial in patients with thin corneas who would otherwise be excluded from riboflavin and UVA cross-linking (Cherfan et al 2013). Another possibility that has been studied in animal models is that of palladium bacteriochlorin 13 0 -(2-sulfoethyl)amide dipotassium salt (WST11) and near-infrared (NIR) illumination.…”
Section: Other Methods Of Cross-linkingmentioning
confidence: 99%
“…The technique halts keratoconus progression without significant complications, however, longer follow-up and studies with larger patient populations are needed to assess the real effectiveness of this technique 64,65 . Other methodologies currently under pre-clinical investigation to facilitate trans-epithelial riboflavin stromal absorption include the use of ultrasound 83 , nano-emulsion systems 84 , and other epithelial permeation enhancers such as d-alpha-tocopheryl poly (ethyleneglycol) 1000 succinate (Vitamin E-TPGS) 85 .…”
Section: Technique Modifications Trans -Epithelial Cross-linking (Te mentioning
confidence: 99%
“…In order to overcome the contra-indication of treating corneas with a thickness bordering on 400ÎŒm, Hafezi and co-workers, and other authors 73,75 replaced the standard iso-osmolar riboflavin solution (containing dextran) with a hypo-osmolar riboflavin solution (without dextran) to swell the cornea to an acceptable thickness prior to cross-linking. Using the modified technique, Hafezi and co-workers 73 treated 20 patients with thin corneas (minimum preoperative stromal thickness of 323ÎŒm) and reported a cessation of keratoconus progression in all cases.…”
Section: Treatment Of Very Thin Kerato-conic Corneamentioning
confidence: 99%